(untitled) (Castilla. Estudios de Literatura, 2023)
This article approaches the poetic work of the Peruvian author José Aburto (1977) from the notion of logoemetics as a form of conceptual access to the interactive mechanisms of the digital textuality and its mediation on the screens. To do so, I outline an approximation to the notions of both logophagy and logoemesis as frameworks to approach the text-visuality and its invisibility and visibility. Thus, through a representative sample of an interactive poems’ corpus, I establish the significant relevance that interfaces and interaction suppose for the reception process of these works in their creative space in an inherent manner.